Electrical brain activations in preadolescents during a probabilistic reward-learning task reflect cognitive processes and behavior strategies - Chung, Yu Sun; Berg, Berry van den; Roberts, Kenneth C.; Bagdasarov, Armen; Woldorff, Marty G.; Gaffrey, Michael S. (Frontiers in Human Neuroscience, 2025)
Both adults and children learn through feedback to associate environmental events and choices with reward, a process known as reinforcement learning (RL). However, tasks to assess RL-related neurocognitive processes in children have been limited. This study validated a child version of the Probabilistic Reward Learning task in preadolescents (8–12 years) while recording event-related-potential (ERPs), focusing on: (1) reward-feedback sensitivity (frontal Reward-related Positivity, RewP), (2) late attention-related responses to feedback (parietal P300), and (3) attentional shifting toward favored stimuli (N2pc). Behaviorally, as expected, preadolescents could learn stimulus–reward outcome associations, but with varying performance levels. Poor learners showed greater RewP amplitudes compared to good learners. Learning strategies (i.e., Win-Lose-Stay-Shift) were reflected by feedback-elicited P300 amplitudes. Lastly, attention shifted toward to-be-chosen stimuli, as evidenced by the N2pc, but not toward more highly rewarded stimuli as in adults. These findings provide novel insights into the neural processes underlying RL in preadolescents.